PENGARUH GOOD CORPORATE GOVERNANCE DAN GREEN INNOVATION TERHADAP KINERJA BERKELANJUTAN PERUSAHAAN - Susanto, Susanto; Sopian, Dani (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2024)
This study aims to analyze the effect of good corporate governance and green innovation on sustainability performance. This study is classified as an associative quantitative study. The type of data used is secondary data obtained from www.idx.co.id and the company's website. The population in this study is the Sri-Kehati Company Listed on the IDX for the 2019-2023 Period. While the sample of this study was determined by the purposive sampling method so that 20 sample companies were obtained. The analysis method used is Panel Data Model Regression analysis. The results of this study indicate that good corporate governance and green innovation have an effect on sustainability performance, good corporate governance has an effect on sustainability performance, green innovation has no effect on sustainability performance.